Factors Affecting the Performance of The Accounting Information System - Muhammad Yusuf (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to analyze the information system user involvement (SI) factor, ability of information system users (SI), information system user education (SI), top management support, organizational structure, organizational culture, and internal control system on the performance of accounting information systems. SIA) at PT. Wijaya Karya Beton Tbk, PPB Boyolali. The object of this research is all employees who use the accounting information system at PT. Wijaya Karya Beton Tbk, PPB Boyolali. This study used a sample of 30 respondents, with data collection techniques using questionnaires, as well as data analysis techniques with Multiple Linear Regression, t-test, F test, and determination coefficient test. The results of this study indicate that the involvement of SI personnel, SI skills, education of SI personnel and internal control systems affect SIA performance, while top management support and organizational structure have no effect on SIA performance at PT. Wijaya Karya Beton, Tbk., PBB Boyolali.